3D Printed Enzymatically Biodegradable Soft Helical Microswimmers - Wang, Xiaopu; Qin, Xiao‐Hua; Hu, Chengzhi; Terzopoulou, Anastasia; Chen, Xiang‐Zhong; Huang, Tian‐Yun; Maniura‐Weber, Katharina; Pané, Salvador; Nelson, Bradley J. (Advanced functional materials, 2018)
Mobile micro‐ and nanorobots are proposed for future biomedical applications, such as diagnostics and targeted delivery. For their translation to clinical practice, biocompatibility and biodegradability of micro‐ and nanorobots are required aspects. The fabrication of small‐scale robots with non‐cytotoxic biodegradable soft components will allow for enhanced device assimilation, optimal tissue interaction and minimized immune reactions. The 3D microfabrication of biodegradable soft helical microswimmers via two‐photon polymerization of the non‐toxic photocrosslinkable hydrogel gelatin methacryloyl (GelMA) is reported. GelMA microswimmers are fabricated with user‐defined geometry and rendered magnetically responsive by decorating their surface with magnetic nanoparticles. In contrast to previous rigid helical microrobots, the soft helical microswimmers can corkscrew above the step‐out frequency with relatively high values of forward velocity, suggesting an unprecedented self‐adaptive behavior. Cytotoxicity assays show the toxicity of GelMA is at least three orders of magnitude lower than that of poly(ethyleneglycol) diacrylates, which are widely used for fabricating hydrogel‐based microswimmers. GelMA microswimmers are fully degradable by collagenases. Furthermore, they support cell attachment and growth, and are gradually digested by cell‐released enzymes during culture. These non‐cytotoxic biodegradable hydrogel microswimmers will greatly expand their applications in medicine by eliminating the concerns of retrieving microrobots after fulfilling tasks in body. Biodegradable soft helical microswimmers are successfully developed based on two‐photon photopolymerization of a gelatin derivative, GelMA. By decorating their surface with magnetic nanoparticles, these microswimmers can be manipulated by magnetic field. Because of the proteolytic cleavage of peptide domains in gelatin, microswimmers made of GelMA can be fully degraded by cell‐secreted proteases.